(untitled) (Romanian Studies Today, 2024)
The present work, part of Formarea cuvintelor în limba română1 [‘Word formation in Romanian’] treaty, was developed by a group of researchers from the Institute of Linguistics ‘Iorgu Iordan – Al. Rosetti’ of the Romanian Academy, and represents the second part of the fourth volume, entitled Sufixele. Derivarea nominală și adverbială [‘Suffixes. Nominal and adverbial derivation’] (2015). The volume’s editor is Blanca Croitor, with Ana-Maria Barbu, Valentina Cojocaru, Ramona Cătălina Corbeanu, Andreea Dinică, Ionuț Geană, Irina Lupu, Carmen Mîrzea Vasile, Magdalena Popescu-Marin, and Oana Stoica-Dinu being part of the research team. This book offers a comprehensive account of the processes behind Romanian word formation.